A CRFD study of supercritical 2 ? 900 MW boilers for Shanghai, P.R. of China. (29th August 2007) - Epple, B.; Benim, A. C.
The tangential pulverized coal firing system of the 2 ? 900 MW boilers for the power plant Wai Gao Qiao in Shanghai, P.R. of China, is computationally investigated. Results have indicated that favourable flow and temperature fields are obtained at full load and part load conditions.